2011
DOI: 10.1080/13607863.2011.569485
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dementia on caring for patients’ diabetes

Abstract: Caregivers of patients with dementia and diabetes face extraordinary challenges managing both conditions and the accompanying BPSD. Their identified need for a greater response from the healthcare system should be tested in quality improvement programs for this overlooked yet rapidly growing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(81 citation statements)
references
References 34 publications
1
80
0
Order By: Relevance
“…72,158 A qualitative study involving the views of 21 caregivers of people with dementia and type 2 diabetes found that behavioural and psychological symptoms of dementia disrupted diabetes care. 102 In addition, carers felt that they received inadequate support in planning their relatives' care, that their contribution to managing their relatives' care was not always recognised and that they were often excluded from decision-making. A systematic review 153 investigating the role of informal caregivers of PLWD found that family carers are often expected to manage medication regimens, the complexity of which are increasing.…”
Section: Views and Experiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…72,158 A qualitative study involving the views of 21 caregivers of people with dementia and type 2 diabetes found that behavioural and psychological symptoms of dementia disrupted diabetes care. 102 In addition, carers felt that they received inadequate support in planning their relatives' care, that their contribution to managing their relatives' care was not always recognised and that they were often excluded from decision-making. A systematic review 153 investigating the role of informal caregivers of PLWD found that family carers are often expected to manage medication regimens, the complexity of which are increasing.…”
Section: Views and Experiencesmentioning
confidence: 99%
“…23,242 Family caregivers of people who have dementia and other health conditions face additional challenges in managing both conditions and dealing with the impact of the accompanying behavioural and psychological symptoms of dementia on care routines. 102 Our study suggests that care pathways need to recognise the contribution of family members and, when available, incorporate their contribution in the care of PLWD. Pathways should include appropriate support for carers that addresses the possibility that carers do not want or cannot absorb the extra responsibilities of caring for someone with a condition such as diabetes.…”
Section: Carer Inclusion and Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…25,28,30,37,39,42,43,45,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] These comprised 79 research papers and 10 guidelines or discussion pieces. Other papers cited in this chapter are for background information and did not undergo full data extraction.…”
Section: Description Of Studiesmentioning
confidence: 99%